ANALISIS SOLVABILITAS PERBANKAN SYARIAH DI INDONESIA PERIODE 2001 – 2004 - Yuliana, SE., MM.,, Indah (Fakultas Ekonomi, UIN Maliki Malang, 2007)
The birth of ‘Syariah Bank’ in Indonesia is really hoped by the Indonesians (especially the Moslems) who think that the interest of the bank is forbidden in Islam. However actually sharing principle in the accounting institution has been known well both in Islamic and non-Islamic countries. ‘Syariah Bank’ is not related with religious rituals (Islam) but it is about a sharing concept in business between the owner of the capital and the capital manager. Bank management with syariah principle can be accessed and managed by all societies and not only by the Moslems. However, it is not debatable that nowadays in Indonesia ‘Syariah Bank’ is developing within the Islamic societies. From this aspect, the opportunity to develop ‘Syariah Bank’ in Indonesia is big enough, as Indonesia is a country having the biggest Moslem followers. ‘Syariah bank’ as an accounting intermediary institution is hoped to be able to give a better performance than the conventional banks. The goodness and the badness of the ‘Syariah Bank’ can be known from its performance reflected from the accounting report. But the accounting report on the Syariah Banking sector is to provide an information related to the accounting position, performance and also accounting position, and bank activities that will be useful for the decision making.This research aims to describe the solvability ability of Syariah Bank in Indonesia based on the banking ratio analysis technique. This is a descriptive research and the population of this research is the Syariah Bank that has been doing IPO in BEJ. The result of the research shows:First, CAR ability from 2001 to 2004 its value is above the determined standard from BI. the CAR that is far above the standard shows that the bank has not used the capital maximally. This can be caused by the bank’s doubt to distribute its capital to the risk ‘assets (aktiva)’. Second, debt to equity from 2001 to 2004 gets increased. It shows that the number of debt year by year gets increased. Third, long term debt to equity from 2001 to 2003 whose values at the syariah banking industry is the smallest is ‘Syariah Mandiri Bank’. While, in 2004 it is ‘Indonesian Muamalat Bank’. It means ‘Syariah Mandiri Bank’ and ‘Indonesian Muamalat Bank’ are the banks which its long term debt composition is under the industrial average, so that the smaller the long term debt to equity ration, the smaller the bank ‘assets (aktiva)’ financed by the long term debt.